FROM THE HISTORY OF CENTRAL ASIAN THINKERS ON NATURE AND ITS CONSERVATION - Fotima Nematova (Social science and innovation, 2024)
In this article, the thoughts of Central Asian thinkers about nature and its protection are presented, his works on nature, and the classification of plants in them are highlighted. Nature protection is thought of as a whole set of activities aimed at rational use of nature and its resources, conscious change of nature for the sake of human interests, preservation and further enrichment of natural resources and nature in general, its beauty, purity